(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2025)
Wi-Fi networks are essential for wireless connectivity in homes, businesses, and public areas. However, many still rely on the outdated Wi-Fi Protected Access 2 (WPA2) protocol, which is well-known to have security weaknesses. These allow attackers to intercept and steal data or gain unauthorized access. While WPA3 offers better security through stronger encryption and authentication, it has not been widely adopted since many older devices do not support it. To address this challenge, we propose a decentralized authentication system that integrates a FreeRADIUS server with a locally hosted validation mechanism. We implemented a private blockchain using Hyperledger Fabric to enable distributed registration and verification of digital identities. As this system does not depend on a central authority, attackers cannot entirely compromise it by targeting single components. Our findings show that, although Hyperledger Fabric adds about 300 milliseconds to the authentication process, communication remains smooth thereafter, indicating that our approach is both practical and secure for device verification on such networks.